2013
DOI: 10.1176/appi.ajp.2013.12111439
|View full text |Cite
|
Sign up to set email alerts
|

The Hotel Study: Multimorbidity in a Community Sample Living in Marginal Housing

Abstract: This marginally housed cohort had greater than expected mortality and high levels of multimorbidity with adverse associations with role function and likelihood of treatment for psychosis. These findings may guide the development of effective health care delivery in the setting of marginal housing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
108
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 84 publications
(116 citation statements)
references
References 57 publications
(55 reference statements)
4
108
0
2
Order By: Relevance
“…Our recent investigations of a large cohort dwelling in this region found that greater drug-related harm was associated with a 1.43-fold increase in multimorbidity (Jones et al, 2013). In the same sample, greater multimorbidity (physical and psychiatric illness) was found to be associated with poorer social and role functioning (The Hotel Study;Vila-Rodriguez et al, 2013). At present, the mortality rate in this sample is 8.29 times what would be expected for an age-and sex-matched Canadian cohort (Jones et al, 2015).…”
Section: Chapter 1 General Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…Our recent investigations of a large cohort dwelling in this region found that greater drug-related harm was associated with a 1.43-fold increase in multimorbidity (Jones et al, 2013). In the same sample, greater multimorbidity (physical and psychiatric illness) was found to be associated with poorer social and role functioning (The Hotel Study;Vila-Rodriguez et al, 2013). At present, the mortality rate in this sample is 8.29 times what would be expected for an age-and sex-matched Canadian cohort (Jones et al, 2015).…”
Section: Chapter 1 General Introductionmentioning
confidence: 66%
“…Indeed, in our initial investigations, nearly half of the Hotel sample met criteria for a neurological illness, with 28% evidencing pathological MRI findings (Vila-Rodriguez et al, 2013). Therefore, this presents as a fruitful investigative angle to better understand the neurobiological vulnerabilities of this population.…”
Section: Chapter 1 General Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Mental illness rates also tend to be significantly higher in the homeless than in the general population [11][12][13][14]. Deinstitutionalization has been named as a possible cause [15], and the inverse association of mental disorders with socioeconomic status has been widely debated [16].…”
Section: Are Substance Use and Mental Illness Associated To An Earliementioning
confidence: 99%